Chromatic edges, surfaces and constancies in cerebral achromatopsia. - Kentridge, R; Heywood, C; Cowey, A (2004)
We tested achromatopsic observer, MS, on a number of tasks to establish the extent to which he can process chromatic contour. Stimuli, specified in terms of cone-contrast, were presented in a three-choice oddity paradigm. First we show that MS is able to discriminate the magnitude of chromatic and luminance contrast, but performance is inferior to that of normal observers. Moreover, MS can discriminate isoluminant borders of different chromatic composition. These abilities are not the result of unintended luminance differences and are abolished when chromatic borders are masked by sharp luminance change. In simple displays, local cone-contrast signals can make a significant contribution to surface colour appearance in normal observers. In more complex displays, the perception of a surface's colour becomes largely independent of the local contrast to its background, via processes presumed to be similar to the edge integration and anchoring stages of Land's Retinex algorithm. We show that in simple displays the percepts of both MS and normal observers are dominated by local chromatic-contrast. But, although the percepts of normal observers change in line with the predictions of retinex theory in more complex displays, those of MS do not, remaining dominated by local contrast signals. We conclude that MS has lost the ability to perform edge integration and that this loss is closely related to his absence of colour experience.